Hybrid Flow Model of Cyber Physical Distribution Network and an Instantiated Decentralized Control Application - Guanhong Chen; Dong Liu (CSEE Journal of Power and Energy Systems)
With the access to large amounts of renewable energy sources (RES), operation uncertainty of distribution networks increases significantly. Fortunately, adopting advanced information and communication technology, a cyber-physical distribution network (CPDS) provides the possibility to solve this problem via aggregative management of decentralized controllable loads. However, information flow in cyber space deeply interacts with energy flow in physical space, leading to a complexity in modeling, design and analysis of the whole control process. To deal with this problem, a general hybrid flow model of CPDS is first proposed in this paper. In this model, the control process is abstracted into interactions among three types of cyber nodes through cyber branches. The mathematic model of cyber nodes and branches is developed as well as that of the controlled physical object for hybrid flow computation. Then, based on the hybrid model, an instantiated application to compensate feeder power deviation caused by RES fluctuation through aggregative control of large-scale air-conditioners (ACs) is investigated. In this application, coordinative control of the AC cluster is achieved through a decentralized control strategy with very little communication cost and very good privacy protection. Results of numerical examples verify the correctness and flexibility of the hybrid flow model in reflecting interactions between cyber flow and energy flow as well as system operations. The proposed decentralized control strategy of the AC cluster is also proven to be effective and robust in FCE compensation.